Everything I am not: Discovering who I am - Gubangxa, Sivenkosi (Centre for Film and Media Studies, 2024)
My research explores the decolonisation of the self by excavating what emerges when the black African woman works to transcend traumatic memory to renew and heal. I suggest that traumatic memory be likened to a scar or a wound on the body. I, a contemporary black South African woman, seek to heal from the wound created by dominant structures of oppression such as slavery, colonialism, patriarchy, and apartheid. I am prompted by the work of black African feminist, Namanzi Choongo Mweene Chinyama (2017), as to how traumatic memory enters our consciousness to distort our understanding of self. I advocate for a process of decolonising which endeavours to break away from structures that inhibited black African women's liberation, denying them their cultural ideologies. Decolonising the self asks us to repossess, take back and re-imagine ourselves by invoking connections to ourselves, our bodies, our ancestors, the land, and others to cultivate inherent knowledge. I use my lived experience to demonstrate how the cultural apparatus of 19th-century racism is still actively created in South African society and globally today. Aspects of this apparatus are the negative stereotypical constructions and myths used to devalue and create ideas of inadequacy in black women to maintain dominance over them. I employ a black African feminist perspective as a framework which encourages placing black women's experiences at the centre of the inquiry. Using a mixed autoethnographic and Practice as Research (PaR) methodology, my research re- imagines representations of black African female experience in South Africa. Thus, it seeks to probe deeper into how implying certain subversions of authoritative hegemonic frames by disturbing accepted social categories and given constructs, creates alternative spaces for the assertion of black African women. I attempt to deconstruct, disturb, and reject normative categorisations to re-construct them, re-claiming, re-imagining, representing, re-discovering, re-shaping and re-membering in the present as a vital part of reclaiming the power of self- definition and healing. Keywords: Black African Women, Trauma, Healing, Decolonisation, Practice as Research, Autoethnography